Innovators and Early Adopters of Distance Education in Social Work - Jo Ann Coe Regan (Advances in Social Work, 2016)
This article highlights the innovators and early adopters of distance education in social work. The past, present and future is discussed as it relates to the evolution of technology innovation in social work education.